Optimization and development of antidiabetic phytosomes by the Box–Behnken design. (3rd April 2018) - Rathee, Sushila; Kamboj, Anjoo
Abstract: Researchers have extensively reviewed on herbs and natural products for their marked clinical efficacy in some recent years, however, maximum of the newly discovered bioactive constituents offer poor bioavailability due to their large size molecules or to their poor miscibility with oils and lipids, thereby limiting their ability to pass across the lipid-rich outer membranes of the enterocytes of the small intestine. Phytosomes are more bioavailable as compared to herbal extracts owing to their enhanced capacity to cross the bio-membranes and thus reaching the systemic circulation. This study was aimed to investigate the development and optimization of antidiabetic phytosomes using a three-factor, three-level the Box–Behnken design (17 batches). The fruits of Citrullus colocynthis (L.) Momordica balsamina and Momordica dioica were extracted using Soxhlet's apparatus. The phytochemical fingerprint profile of the combined methanolic extracts was done by using high-performance thin layer chromatography (HPTLC). The polynomial quadratic equation analysis was designed to study the response (entrapment efficiency (EE), % yield) of independent significant factors at different levels. Phytosomes were characterized in terms of drug content, particle size, EE, zeta potential and in vitro dissolution. TEM analysis revealed good stability and a spherical, self-closed structure of phytosomes in complex formulations. Average particle size was found to 450 nm. Total flavonoid content was found to be 10.0 ± 0.002 μg/g. Optimized formulation was selected and was prepared using A (1:3), B (60 °C) and C (2.5 h) to give maximum yield and entrapment efficiencies (72% and 92.1 ± 5.1%). Phytosomes were found to have antidiabetic activity comparable to metformin in low dose. HPTLC showed the presence of the phyto-constituent quercetin.